2021
DOI: 10.3390/metabo11090580
|View full text |Cite
|
Sign up to set email alerts
|

Emersion and Relative Humidity Modulate Stress Response and Recovery Dynamics in Juvenile Mussels (Perna canaliculus)

Abstract: The early stages of intertidal mussels, including the green-lipped mussel, Perna canaliculus, face both direct and indirect environmental threats. Stressors may influence physiological status and, ultimately, survival. An understanding of the nature of stress experienced is critical to inform conservation and aquaculture efforts. Here, we investigated oxidative stress dynamics in juvenile P. canaliculus in relation to emersion duration (1–20 h) and relative humidity (RH, 29–98%) by quantifying oxidative damage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 67 publications
0
14
0
Order By: Relevance
“…Overall, this study showed that the ROS detection protocol performed on juvenile P. canaliculus effectively distinguished differences in environmentally induced stress levels through quantification of the ROS signal in terms of area of coverage. While emersion stress in juvenile P. canaliculus has previously been shown to result in the accumulation of oxidative damage markers ( Delorme et al, 2019 , 2021a ), as a consequence of increased ROS in the cells ( Freire et al, 2012 ), the direct ROS quantification presented in the present study reveals complex kinetics that warrant further investigation. Additionally, future research would also benefit from exploring alternative fluorogenic probes to gain more insight to the origins of ROS production.…”
Section: Resultsmentioning
confidence: 51%
See 4 more Smart Citations
“…Overall, this study showed that the ROS detection protocol performed on juvenile P. canaliculus effectively distinguished differences in environmentally induced stress levels through quantification of the ROS signal in terms of area of coverage. While emersion stress in juvenile P. canaliculus has previously been shown to result in the accumulation of oxidative damage markers ( Delorme et al, 2019 , 2021a ), as a consequence of increased ROS in the cells ( Freire et al, 2012 ), the direct ROS quantification presented in the present study reveals complex kinetics that warrant further investigation. Additionally, future research would also benefit from exploring alternative fluorogenic probes to gain more insight to the origins of ROS production.…”
Section: Resultsmentioning
confidence: 51%
“…Juvenile P. canaliculus can be stranded by the receding tide or exposed to air during transfer from the hatchery to grow-out facilities in aquaculture ( Delorme et al, 2020 ; Jeffs et al, 2018 ). Additionally, emersion in juvenile P. canaliculus has shown to result in high oxidative damage, particularly after 1 h of rehydration after emersion ( Delorme et al, 2021a ). Hence, the present study applied emersion and relative humidity treatments as relevant stressors likely to induce a range of ROS levels in P. canaliculus juveniles ( Figs 1 and 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations